Adsorption Capacities of Iron Hydroxide for Arsenate and Arsenite Removal from Water by Chemical Coagulation: Kinetics, Thermodynamics and Equilibrium Studies - Muhammad Ali Inam (MDPI AG, 2021)
Arsenic (As)-laden wastewater may pose a threat to biodiversity when released into soil and water bodies without treatment. The current study investigated the sorption properties of both As(III, V) oxyanions onto iron hydroxide (FHO) by chemical coagulation. The potential mechanisms were identified using the adsorption models, ζ-potential, X-ray diffraction (XRD) and Fourier Transform Infrared Spectrometry (FT-IR) analysis. The results indicate that the sorption kinetics of pentavalent and trivalent As species closely followed the pseudo-second-order model, and the adsorption rates of both toxicants were remarkably governed by pH as well as the quantity of FHO in suspension. Notably, the FHO formation was directly related to the amount of ferric chloride (FC) coagulant added in the solution. The sorption isotherm results show a better maximum sorption capacity for pentavalent As ions than trivalent species, with the same amount of FHO in the suspensions. The thermodynamic study suggests that the sorption process was spontaneously exothermic with increased randomness. The ζ-potential, FT-IR and XRD analyses confirm that a strong Fe-O bond with As(V) and the closeness of the surface potential of the bonded complex to the point of zero charge (pHzpc) resulted in the higher adsorption affinity of pentavalent As species than trivalent ions in most aquatic conditions. Moreover, the presence of sulfates, phosphates, and humic and salicylic acid significantly affected the As(III, V) sorption performance by altering the surface properties of Fe precipitates. The combined effect of charge neutralization, complexation, oxidation and multilayer chemisorption was identified as a major removal mechanism. These findings may provide some understanding regarding the fate, transport and adsorption properties onto FHO of As oxyanions in a complex water environment.